Evaluation of new immunological targets in neuromyelitis optica. (28th November 2012) - Chanson, Jean‐Baptiste; Paolini, Ilaria; Collongues, Nicolas; Alcaro, Maria C.; Blanc, Frédéric; Barbetti, Francesca; Fleury, Marie; Peroni, Elisa; Rovero, Paolo; Rudolf, Gabrielle; Lolli, Francesco; Trifilieff, Élisabeth; et al.
<x xml:space="preserve">Abstract</x> The detection of reactivity against autoantigens plays a crucial role in the diagnosis of autoimmune diseases. However, only a few autoantibodies are known in each disease, and their precise targets are often not precisely defined. In neuromyelitis optica (NMO), an autoimmune disease of the central nervous system, anti‐aquaporin 4 antibodies are currently the only available immunological markers, although they are not detected in 10–50% of patients. Using enzyme‐linked immunosorbent assays, we evaluated the reactivity against 19 structurally defined peptides in 26 NMO sera compared with 21 healthy subjects. We observed increased levels of IgG against myelin basic protein sequence MBP(156–175), pyruvate dehydrogenase sequence PDH(167–186) and CSF114(Glc), the last of these having a possible correlation with onset of inflammatory relapse. These preliminary results may suggest that the aquaporin 4 is not the unique target in NMO and that the study of reactivity against these peptides would be helpful for the diagnosis and follow‐up of the disease. Complementary studies are however warranted to confirm these results. Copyright © 2012 European Peptide Society and John Wiley & Sons, Ltd.